STUDI TENTANG PERILAKU AGRESIF SISWA DI SEKOLAH - Restu, Yoshi; Yusri, Yusri; Ardi, Zadrian (Konselor, 2013)
Teens are developing will show a positive attitude. In fact, most adolescents exhibit negative behaviors, one of which aggressive behavior. This study aims to gain an overview of types of aggressive behavior, aggressive behavior and the factors that cause counselors attempt to address students' aggressive behavior. This research is a qualitative case study approach, with the finding that subjects behave aggressively, there are four factors that cause aggressive behavior of students, assistance can be given related to the aggressive behavior of students is to provide services BK.